2005
DOI: 10.1016/j.seizure.2004.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of epilepsy its treatment gap and knowledge, attitude and practice of its population in sub-urban Senegal an ILAE/IBE/WHO study

Abstract: A door-to-door survey was used to determine the prevalence of epilepsy among 4500 people within the Pikine Health District (population 480,000) Senegal. Prevalence was 14.2/1000, and 23.4% of all people with epilepsy had never received appropriate treatment. Figures for the prevalence had increased since a previous survey in 1989. In parallel a study of knowledge attitude and practice was performed in the same district. Salient findings were that: two-thirds of interviewees had at some time witnessed a seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 15 publications
7
62
2
1
Order By: Relevance
“…Recent trends in research into African plant uses, show that traditional medicine is commonly used to treat neurological disorders in the West African region, and some recent publications are available, namely for Nigeria [29], Gambia [30], Senegal [31], and Cameroon [26,32]. However, there are still very few studies on this subject for Guinea-Bissau [17].…”
Section: Resultsmentioning
confidence: 99%
“…Recent trends in research into African plant uses, show that traditional medicine is commonly used to treat neurological disorders in the West African region, and some recent publications are available, namely for Nigeria [29], Gambia [30], Senegal [31], and Cameroon [26,32]. However, there are still very few studies on this subject for Guinea-Bissau [17].…”
Section: Resultsmentioning
confidence: 99%
“…28,29 Similarly, select populations in low-income countries had surprisingly small gaps; suburban and urban populations in India, Madagascar and Senegal had treatment gaps of less than 30%. 21,[30][31][32] Direct comparisons of treatment gaps over time were difficult to carry out because of differences in study methods and populations. In Ethiopia, two studies in the same population in which the same methods were used showed a gap of 98% in 1986-1988 and a gap of 87% among new cases identified during a repeat survey in 1990.…”
Section: Lower Middle Incomementioning
confidence: 99%
“…Demonstration projects have been carried in China [4], Togo [56], Brazil [9], Senegal [6], and Vietnam [17•].…”
Section: Carementioning
confidence: 99%